O-047 Intervention verses observation for borden type 1 intracranial dural arteriovenous fistula: a pooled analysis of 540 patients. (23rd July 2022) - Schartz, D; Rahmani, R; Gunturi, A; Kohli, G; Akkipeddi, S; Ellens, N; Bhalla, T; Mattingly, T; Bender, M
Abstract : Introduction: It is thought that Borden Type 1 intracranial dural arteriovenous fistula (dAVF) have a benign clinical course and yet a majority are treated in reported series. It remains unclear if intervention or observation confers superior clinical outcomes in these patients. Methods: A PRISMA guided systematic literature review and meta-analysis was completed to evaluate the outcomes of intervention of any type verses observation alone in the management of low-grade, Borden Type 1 intracranial dAVF. Data from comparative studies were collected from the literature and pooled together with the authors' own institutional experience. Primary outcome measures included: grade progression, worsening symptoms, death due to dAVF, permanent complications other than death (i.e. from intracerebral hemorrhage or intervention), and rate of death combined with permanent complication. Spontaneous obliteration and procedural complications were also calculated as secondary outcome measures. A fixed effects model was used to calculate pooled odds ratios (OR) for each outcome variable. Rates of non-comparative variables were also calculated. Results: The systematic review yielded 5 comparative studies, that when combined with our experience resulted in a total of 540 patients included in the meta-analysis. The intervention group included 314 patients, while the observation group included 226 patients. There was no significant difference in grade progression (OR: 2.02, 95% CI: 0.51 to 8.03, P = 0.32, I 2 = 8%), nor in deaths due to dAVF (OR: 3.81, CI: 0.61 to 23.84, P = 0.15, I 2 = 0%). However, patients within the intervention group had a higher odds of worsening symptoms after intervention (OR: 2.18, CI: 1.08 to 4.43, P = 0.03, I 2 = 0%). Additionally, intervention was associated with a higher odds of death or permanent complication from either hemorrhage or intervention (OR: 4.35, CI: 1.00 to 19.08, P = 0.05, I 2 = 0%). Any type of procedural complication occurred in 45/303 (14.9%) patients, with a permanent complication in 9/310 (2.9%) patients. There were no instances (0%) of permanent complications (other than death) due to rupture in either group. Spontaneous obliteration occurred in 24/122 (19.7%) of the observed patients. Conclusions: Pooled analysis of patients with low-grade, Borden Type 1 intracranial dAVF indicates that intervention results in a higher odds of symptom progression, and death or permanent procedural complication. These findings suggest that observation could be favored and patients should be selected for intervention judiciously. Disclosures: D. Schartz: None. R. Rahmani: None. A. Gunturi: None. G. Kohli: None. S. Akkipeddi: None. N. Ellens: None. T. Bhalla: None. T. Mattingly: None. M. Bender: None.